Efficacy and safety of neoadjuvant therapy with tislelizumab plus axitinib for nonmetastatic renal cell carcinoma with inferior vena cava tumor thrombus: a retrospective study - Zhongjie Zhao; Zhengsheng Liu; Kaiyan Zhang; Wei Li; Lijian Zhang; Bingliang Jiang; Bin Chen; Jinchun Xing; Xuegang Wang (Scientific Reports)
Abstract In renal cell carcinoma (RCC) patients with inferior vena cava (IVC) tumor thrombus, neoadjuvant therapy could alleviate the burden of tumor thrombus, enhance the safety and feasibility of surgical resection, and improve patient prognosis. The combination of tislelizumab and axitinib has demonstrated efficacy in the treatment of advanced RCC. Our study aimed to evaluate the efficacy and safety in the neoadjuvant therapy setting of tislelizumab and axitinib in RCC patients with IVC tumor thrombus. In this retrospective study, seven patients of nonmetastatic RCC with IVC tumor thrombus who received 3 cycles of neoadjuvant therapy with tislelizumab plus axitinib at the First Affiliated Hospital of Xiamen University from May 2020 to December 2023 were included. The main outcomes included objective response rate (ORR), reduction of tumor thrombus size and level, surgical outcomes, and adverse events (AEs). The median age was 66 (range, 50–72) years, and five (71.4%) patients were male. Five (71.4%) patients were diagnosed with clear cell carcinoma, and two (28.6%) patients were papillary type I carcinoma. Four (57.1%) patients had level II tumor thrombus and three (42.9%) patients had level III. The ORR of patients was 57.1%. The mean decrease in thrombus diameter and length was 5.8 (1.8–17.2) mm and 18.5 (4.4–41.5) mm, respectively. All patients showed a decrease in IVC tumor thrombus. The mean time from the end of neoadjuvant therapy to radical nephrectomy and thrombectomy was 31.7(range, 22–45) days. No intraoperative complications or postoperative Clavien-Dindo grade>3 complications occurred. The most common AEs were all grade 1–2, and only one patient had grade 4 hepatic impairment. No AEs delayed the surgery schedule. This study of RCC patients receiving neoadjuvant combination with tislelizumab and axitinib effectively reduced primary tumor and IVC tumor thrombus with the absence of serious AEs, demonstrating a promising neoadjuvant therapy.